(untitled) (Research, Society and Development, 2022)
Objective: To publicize the By Your Side (BYS) application to promote occupational health and highlight the importance of project continuity for application validation. Methodology: Methodological study of an applied nature in the technological production version, carried out at HU-UFS. The application was produced from July 2020 to April 2021 and followed the following steps: textual preparation of the material; mapping of requirements for the development of the application; screen prototyping and development of the first version of the system. The application validation phase will begin and will use the System Usability Scale (SUS) and the construction of the validation protocol for this computational tool. Results: BYS is an occupational health promotion application, available in the Android version, which offers various activities, such as nutritional guidelines, physical exercises, relaxation techniques, mental health care, guidance on care with professionals, dissemination of programs of the institution, medication alerts, calculators for the Body Mass Index (BMI) and water intake, entertainment, diary of notes and forum with groups and rooms. Conclusion: BYS has the potential to help health professionals, promoting a healthier life and relieving the stress load of work through various activities related to physical and mental health. In this way, the validation of the application is of paramount importance so that, soon, it will be implemented and monitored in health institutions, improving the quality of personal and professional life of health professionals.